INvestigational Vertebroplasty Efficacy and Safety Trial (INVEST): a randomized controlled trial of percutaneous vertebroplasty - Gray, Leigh A; Jarvik, Jeffrey G; Heagerty, Patrick J; Hollingworth, William; Stout, Lydia; Comstock, Bryan A; Turner, Judith A; Kallmes, David F (BMC musculoskeletal disorders, 2007)
The treatment of painful osteoporotic vertebral compression fractures has historically been limited to several weeks of bed rest, anti-inflammatory and analgesic medications, calcitonin injections, or external bracing. Percutaneous vertebroplasty (the injection of bone cement into the fractured vertebral body) is a relatively new procedure used to treat these fractures. There is increasing interest to examine the efficacy and safety of percutaneous vertebroplasty and to study the possibility of a placebo effect or whether the pain relief is from local anesthetics placed directly on the bone during the vertebroplasty procedure. Our goal is to test the hypothesis that patients with painful osteoporotic vertebral compression fractures who undergo vertebroplasty have less disability and pain at 1 month than patients who undergo a control intervention. The control intervention is placement of local anesthesia near the fracture, without placement of cement. One hundred sixty-six patients with painful osteoporotic vertebral compression fractures will be recruited over 5 years from US and foreign sites performing the vertebroplasty procedure. We will exclude patients with malignant tumor deposit (multiple myeloma), tumor mass or tumor extension into the epidural space at the level of the fracture. We will randomly assign participants to receive either vertebroplasty or the control intervention. Subjects will complete a battery of validated, standardized measures of pain, functional disability, and health related quality of life at baseline and at post-randomization time points (days 1, 2, 3, and 14, and months 1, 3, 6, and 12). Both subjects and research interviewers performing the follow-up assessments will be blinded to the randomization assignment. Subjects will have a clinic visit at months 1 and 12. Spine X-rays will be obtained at the end of the study (month 12) to determine subsequent fracture rates. Our co-primary outcomes are the modified Roland score and pain numerical rating scale at 1 month. Although extensively utilized throughout North America for palliation of pain, vertebroplasty still has not undergone rigorous study. The study outlined above represents the first randomized, controlled study that can account for a placebo effect in the setting of vertebroplasty. Current Controlled Trials ISRCTN81871888.